Theory of coal wall spalling and cooperative control by “support-destressing” in 10 m ultra-large mining height working face - Jiangbin LIU; Zhizeng HUANG; Qianjin LIU; Zhen ZHANG; Cundi HAN; Xingyu LIN; Rongshan MA; Zhen ZHAO (Meitan xuebao)
Coal wall spalling is one of the main factors restricting the safe production of 10 m ultra-large mining height working face.In response to the problem of unclear mechanism of coal wall spalling and difficult control of surrounding rock in the 10 m ultra-large mining height working face, The characteristics of coal wall spalling in ultra-high mining height working faces were measured. The influence law and mechanism of horizontal stress unloading on the failure and instability of ultra-high coal walls in brittle coal bodies were studied, and the principle of cooperative control by “support-destressing” in ultra-large mining height working face was proposed. The research results indicate that the coal wall spalling of the 10m ultra high mining face is mainly in the form of a “half moon” shape and a “sloping step” shape, and the periodic pressure of the mining face exacerbates the instability of the coal wall spalling. Coal wall spalling is the result of mining stress. The plastic damage of coal in front of coal wall mainly occurs in the post-peak unloading stage of advance abutment pressure.In this stage, the horizontal stress and lateral pressure coefficient exhibit a gradient attenuation change. Because the middle part of the coal wall experiences weaker clamping action from the roof and floor, resulting in the greatest attenuation of horizontal stress. As the mining height increases, the degree of horizontal stress unloading in front of the coal wall significantly increases. The reduction in confining pressure caused by horizontal stress unloading is the primary controlling factor for the failure and instability of ultra-high coal walls in brittle fractured coal and rock masses, The reduction in confining pressure caused by horizontal stress unloading is the primary controlling factor for the failure and instability of ultra-high coal walls in brittle fractured coal and rock masses. The failure of coal wall preferentially develops in the direction of the maximum horizontal stress unloading degree and the minimum lateral pressure coefficient. Based on this, the transfixion trajectory of micro-fracture group in coal wall was obtained, and the mechanism of “half-moon” and “slope-step” spalling in coal wall was explained. By reducing the roof load acting on the coal wall and increasing the horizontal support force of the coal wall, the damage and failure of the coal wall in the ultra-large mining height working face can be slowed down, and the collaborative control technology of “high strength support-large flow fracturing pressure relief ” was formed. The problem of strong mine pressure appearance and coal wall spalling in the 10 m ultra-large mining height working face was effectively controlled.